A Comprehensive Biological and Clinical Perspective Can Drive a Patient-Tailored Approach to Multiple Myeloma: Bridging the Gaps between the Plasma Cell and the Neoplastic Niche. (18th May 2020) - Solimando, Antonio Giovanni; Vacca, Angelo; Ribatti, Domenico
Abstract : There is a broad spectrum of diseases labeled as multiple myeloma (MM). This is due not only to the composite prognostic risk factors leading to different clinical outcomes and responses to treatments but also to the composite tumor microenvironment that is involved in a vicious cycle with the MM plasma cells. New therapeutic strategies have improved MM patients' chances of survival. Nevertheless, certain patients' subgroups have a particularly unfavorable prognosis. Biological stratification can be subdivided into patient, disease, or therapy-related factors. Alternatively, the biological signature of aggressive disease and dismal therapeutic response can promote a dynamic, comprehensive strategic approach, better tailoring the clinical management of high-risk profiles and refractoriness to therapy and taking into account the role played by the MM milieu. By means of an extensive literature search, we have reviewed the state-of-the-art pathophysiological insights obtained from translational investigations of the MM-bone marrow microenvironment. A good knowledge of the MM niche pathophysiological dissection is crucial to tailor personalized approaches in a bench-bedside fashion. The discussion in this review pinpoints two main aspects that appear fundamental in order to gain novel and definitive results from the biology of MM. A systematic knowledge of the plasma cell disorder, along with greater efforts to face the unmet needs present in MM evolution, promises to open a new therapeutic window looking out onto the plethora of scientific evidence about the myeloma and the bystander cells.